Gambaran Pemahaman Ibu-Ibu tentang Stunting di Desa Emplasmen Kwala Mencirim - Aminah Cinda Kasih; Jurani Jurani; Robiatul Adawiyah Rangkuti; Yuka Fadhilla; Luri Resti Fauzia; Neni Zahrani Wijaya; Ammamiarihta Ammamiarihta (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Stunting is a developmental disorder in children caused by poor nutrition, repeated infections, and inadequate psychosocial stimulation. A child can be defined as stunted if his age height is more than two standard deviations, below the provisions of the Child Growth Standard. The high incidence of stunting in Indonesia is one of the factors due to people's misunderstanding about stunting where they consider it reasonable about the proportion of their children's height, the mother's understanding factor is a very important factor in preventing stunting where stunting in children tends to occur in mothers who have less understanding. Understanding from mothers/expectant mothers really needs to be improved optimally to prevent and break the chain of stunting.